CHARACTERISTIC OF ADAPTATIVE REACTIONS IN CHILDREN WITH CHRONIC PATHOLOGY OF DIGESTIVE TRACT - K. V. Lasuk; N. O. Malynovska; N. V. Моvlyanova (Zaporožskij Medicinskij Žurnal)
Nowadays diseases of digestive organs in children are significant medico-social problem. It is known that adaptive reactions in many respects determine morbidity, severity of disease, effectiveness of medical treatment.